If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(s + -90) = -50 Reorder the terms: 4(-90 + s) = -50 (-90 * 4 + s * 4) = -50 (-360 + 4s) = -50 Solving -360 + 4s = -50 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '360' to each side of the equation. -360 + 360 + 4s = -50 + 360 Combine like terms: -360 + 360 = 0 0 + 4s = -50 + 360 4s = -50 + 360 Combine like terms: -50 + 360 = 310 4s = 310 Divide each side by '4'. s = 77.5 Simplifying s = 77.5
| (5x-6)(x^2-4x-1)= | | (4x^2)-47+70=0 | | M-52=27 | | 3(v+2)=12 | | 3(b+1)+1=10 | | 3(z+-15)=-60 | | 25-w=46 | | 16=-2(n+-17) | | m^2-n^2-am-an=0 | | 6-2x=-20 | | 15p+19.96=-14.08+11.3p | | 2(3r-7)-(2+r)= | | -11.4u-3.54+19.2u=8.34+8.9u | | -5.6k-16.61=-4.5k | | -13.03+5.1m=12.3m+10.01 | | -12.2w+16.74=-13.6w-7.2 | | 11.5d=-7.56+10.3d | | -6.5u+18.93=1.18-12.8u-8.08 | | -8.53-5+19.5z=18.1z-19.97 | | 7.82-1.5g=11.8g-16.12 | | -8.53-5+19.5z=18.1-19.97 | | -5s+16+12=-17-10s | | -4b+20=-18-b-19 | | -10j=19-11j | | 5n-6=6n+11 | | 2(22-8)=22+6 | | (z^(-1/2)z^(5/2))/(z^(1/3)) | | 10+6-3r=-10+10r | | 12(12k+11)=12(12k+12) | | 6x-35=71 | | 2(y-8)=y+6 | | 2.5=ln(7/x) |